In-Silico Analysis of Polyphenol Compounds in Pomegranate Fruit (Punica granatum L.) Peel Potential as type 2 Antidiabetes Mellitus - ummah, khoirotul; Jariyah, Ita Ainun (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Diabetes mellitus is a disease characterized by increased blood sugar levels due to insulin resistance caused by the uncontrolled expression of the protein tyrosine phosphatase 1B (PTP1B). Several compounds that inhibit PTP1B have been studied, including polyphenol. Many studies have been conducted on diabetes medicines based on natural ingredients, including the pomegranate fruits (Punica granatum L). This study aims to test the inhibitory activity of polyphenolic compounds in pomegranate peel (gallic acid, caffeic acid, ellagic acid, chlorogenic acid, apigenin, quercetin, pelargonidin, and cyanidin) against PTP1B through molecular docking. The 3D structures of polyphenolic compounds were obtained from the PubChem database, while PTP1B was from the Protein Data Base. Molecular docking simulations were carried out using AutoDock Vina and several supporting softwares, such as Biovia Discovery Studio Client 4.1, AutoDockTools 1.5.6, PyMOL, and LigPlot. Molecular docking results showed that polyphenolic compounds from pomegranate peel have good inhibitory potential against PTP1B. It is proven by the binding affinity value for PTP1B, which is low and negative, namely in the range -6.4 to -8.4 kcal/mol, and the inhibition constant in the range 0.69 to 20,12 µM. The presence of phenol and carboxylic acid groups in polyphenol compounds can strengthen ligand-protein complexes through hydrogen bonds, especially with the amino acid residues Gln221 and Cys215. The potential of polyphenolic compounds as antidiabetics is also supported by van der Waals interactions and π-π stacking interactions with PTP1B. Based on the molecular docking test that has been carried out, it can be concluded that the polyphenolic compounds in pomegranate peel have the potential to act as type 2 anti-diabetes mellitus.